The Effectiveness of RPT (Repetitive-Practice Technique) In Teaching Speaking Ability - Hanofi Harianto; Hizbul Wathoni; Ridwan Ridwan; Selamet Riadi Jaelani (Educatio, 2022)
This research aims to know the significant effect of RPT (Repetitive-Practice Technique) in teaching speaking at the tenth-grade students of SMA Al-Hasaniyah NW Jenggik in 2016-2017. This research was designed as pre-experimental with pretest and posttest design. The study population was 27 and 27 as the sample in X chosen by purposive random sampling it means the sample was taken purposively because the sample is representative. Speaking tests and analytical scoring rubric were used to collect the data. Then the data were analyzed using descriptive statistics and paired sample t-test to test the hypothesis, and it was performed by SPSS 22 for windows. The descriptive statistics analysis showed that RPT (Repetitive-Practice Technique) was effective in teaching speaking ability. It was proven by improving students' scores from 40.89 in Pre-Test and 58.96 in Post-Test. While the result of hypothesis testing using paired sample t-test at significance (2-tailed) value level was .000, it was lower than .05. RPT (Repetitive-Practice Technique) is significantly effective in teaching speaking ability. It was suggested that speaking in RPT (Repetitive-Practice Technique) is suitable for teaching speaking.